The Role of Local Government Leaders in Public Policy Process: A Case Study of Khunthale Municipality Muang District, Suratthani Province - Suanthong, Pennapha (Journal of Humanities and Social Sciences Suratthani Rajabhat University, 2023)
This research article aimed to study the communities’ opinions, analyze the local communities’ roles, and suggest the public policy process of Khunthale municipality, Muang district, Suratthani province. The participants were 388 people in Khunthale who used questionnaires in the public policy process. The key informants were ten administrators, the local council, the municipality staffs, and the community leaders. The questionnaire on the community leaders’ role in the public policy process and group discussion included 15 leaders and people in the municipality’s area. Qualitative data were analyzed using descriptive statistics such as mean and standard deviation, and quantitative data by analyzing content and interpreting data. The findings revealed that 1) people’s perceptions of the public policy process were high (x=3.69), policy evaluation was high (x=3.71), policy formulation was high (x=3.69), and policy implementation was low (x=3.67), although all other aspects were high, and 2) the administrators’ and local council’s roles in the public policy process found that the local administrator and the local council had to take a role in creating public policy in three processes: (1) policy formulation by making a public hearing to create a community development plan; (2) policy implementation through an effective approval plan of the local council based on its objective and goal; (3) policy evaluation through evaluating the policy and controlling the governor to report the policy result and effect of the project; and (4) people’s recommendations to the local municipality cabinet in pushing for the actual implementation of the policy into practice and transparency. It was also distributing the development budget equitably and fairly, so the public could access information and be able to verify it.